Investigation of bio polymer electrolyte based on cellulose acetate-ammonium nitrate for potential use in electrochemical devices. (10th February 2017) - Monisha, S.; Mathavan, T.; Selvasekarapandian, S.; Milton Franklin Benial, A.; Aristatil, G.; Mani, N.; Premalatha, M.; Vinoth pandi, D.
Highlights: Biopolymer electrolytes based on cellulose acetate (CA)-NH4 NO3 were newly developed. 50CA:50NH4 NO3 exhibits high ionic conductivity 1.024 × 10 −3  S cm −1 at room temperature. IR spectral analyses were carried out by experimental and computational methods. Comparison of output voltage and power performance for single fuel cell application. Abstract: Proton conducting materials create prime interest in electro chemical device development. Present work has been carried out to design environment friendly new biopolymer electrolytes (BPEs) using cellulose acetate (CA) complex with different concentrations of ammonium nitrate (NH4 NO3 ), which have been prepared as film and characterized. The 50 mol% CA and 50 mol% NH4 NO3 complex has highest ionic conductivity (1.02 × 10 −3  S cm −1 ). Differential scanning calorimetry shows the changes in glass transition temperature depends on salt concentration. Structural analysis indicates that the highest ionic conductivity complex exhibits more amorphous nature. Vibrational analysis confirms the complex formation, which has been validated theoretically by Gaussian 09 software. Conducting element in the BPEs has been predicted. Primary proton battery and proton exchange membrane fuel cell have been developed for highest ionic conductivity complex. Output voltage and power performance has been compared for single fuel cell application, which manifests the present BPE holds promise application in electrochemical devices.